ANALISIS POTENSI SEKTOR EKONOMI UNGGULAN DI SUMATERA SELATAN - Widy Astuti (Department of Development Economics, Universitas Sriwijaya, 2005)
The purpose of this research is to analyze about potency of leading economic sector in South Sumatera and to know the impact of economic growth of South Sumatra. The technique analysis used in this research is qualitative and quantitative analysis and the tools of the analysis are Location Quotient and multiple linear regression. Result of this research shows three leading economic sector in South Sumatra, such as: Mining and Quarrying sector, Agriculture sector, and Restaurant, Hotel and Trade Sector. The leading sector respectively were economic growth of South Sumatra, in coefficient correlation = 88,6%. Its means between independent variables (Mining ang Quarrying sector, Agriculture sector, and Restaurant, Hotel and Trade sector) and dependent variables (South Sumatra's growth economic) is significant.Keywords: Leading Economic Sector, Growth Economic